Pengaruh Kualitas Pelayanan, Citra Destinasi, dan Promosi terhadap Kepuasan Pengunjung Monumen Yogya Kembali - Rahmawati, Pradita Dwi; Wahyuningsih, Tri Harsini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This study was conducted to determine the influence of service quality, destination image, and promotion on visitor satisfaction at Monumen Yogya Kembali. This research is quantitative research with data sources using primary data. The sample was determined by non-probability sampling using a purposive sampling method, namely visitors to the Monumen Yogya Kembali who visited at least twice. The number of samples in this study was 80 respondents. Data was collected using a questionnaire distributed via google form. After going through instrument testing, basic assumption testing, and classical assumption testing, hypothesis testing is carried out. From the result of the t test and multiple regression analysis, a significance result of 0,003 was obtained with a coefficient of 0,195 for service quality; a significance of 0,001 with a coefficient of 0,386 for destination image; and a significance of 0,000 with a coefficient of 0,295 for promotion. Based on these results, it means that service quality, destination image, and promotion partially have a positive and significant effect on visitor satisfaction at Monumen Yogya Kembali. These three variables have an influence of 81,2% on visitor satisfaction.